THE INFLUENCE OF LMX QUALITY AND ORGANIZATIONAL CULTURE TOWARD ORGANIZATIONAL COMMITMENT OF EMPLOYEES AT PT INDOMARCO PRISMATAMA PONTIANAK - AZIZ, Nur Aziz Hidayat B1024141003 (Jurnal Manajemen Update, 2019)
The purpose of this study was to determine the description of leader member exchange, organizational culture and organizational commitment at PT Indomarco Prismatama Pontianak and analyze how much the influence of leader member exchange quality and organizational culture toward organizational commitment. The sample in this research was 100 employees from PT Indomarco Prismatama Pontianak.The measurement of this study is using a Likert scale and analyzed using SPSS 22. The tests which have been done are validity, reliability, classic assumption test, R square test and T test in order to analyze the relationship of all variables. Based on the research result, it can be known that leader member exchange and organizational culture had positive and significant relationship on organizational commitment with coefficient of determination as much as 40 percent, while the other 60 percent is influenced by other variables which were not been analyzed in this research. Keywords: Leader Member Exchange, Organizational Culture, Organizational Commitment BIBLIOGRAPHYAllen, N. J., & Meyer, J. P. (1990). The measurement and antecedents of affective, continuance and normative commitment to the organization. Journal of occupational psychology, 63(1), 1-18.Amirullah., & Budiyono, H. (2004). Pengantar Manajemen. Yogyakarta: Graha Ilmu.Anggriawan, D.A. (2012). Hubungan antara Leader-Member Exchange dan Kepuasan Kerja pada Karyawan bagian Operasional PT. Krakatau Steel (Persero) Tbk. (Unpublished Thesis), Universitas Indonesia.Berberoglu, A. (2018). Impact of organizational climate on organizational commitment and perceived organizational performance: empirical evidence from public hospitals. BMC Health Services, Vol 18:399.Casimir, G. (2016). The Relationships Amongst Leader member Exchange, Perceived Organizational Support, Affective Commitment, And In-Role Performance. Leadership & Organization Development Journal, Vol.35, 366-385.Dewi, I., & Surya, I. (2017). Pengaruh Budaya Organisasi Terhadap Komitmen Organisasional Dan Organizational Silence Pada Pt. Pln (Persero) Rayon Denpasar. E-Jurnal Manajemen Universitas Udayana, 6(1)Dyne, V.L., & Graham, J.W., (2005). Organizational Citizensip Behaviour; Construct Refeiniton Measurement and Validation. Academy Management Journal. Vol.37 (4). 765-802.Ernawan, E. R. (2011). Budaya Organisasi dalam Perspektif Ekonomi dan Bisnis. Bandung: Alfabeta.Ferdinand, A. (2002). Structural Equation Modelling dalam Penelitian Manajemen. Semarang: FE UNDIP.Gerstner, C. R., & Day, D. V. (1997). Meta-Analytic review of leader?member exchange theory: Correlates and construct issues. Journal of Applied Psychology, Vol.82 (6), 827-844.Ghozali, I. (2005). Aplikasi Analisis Multivariate dengan SPSS. Semarang: UNDIP.Graen, G.B., & Uhl-Bien, M. (1995). Relationship-Based Approach to Leadership: Development and Leader-Member Exchange (LMX) Theory of Leadership over 25 Years: Applying a Multi-Level Multi-Domain Perspective. Leadership Quarterly, Vol.6, 219-247.Haryanti, K. (2008). New Workers and Their Supervisors in Central Java Organizations: The LMX Java Project. (Dissertation), Netherland: University of Nijmegen.Haryanti, K. (2008). Tinjauan terhadap Leader-Member Exchange (LMX) sebagai Salah Satu Teori Leadership Modern. Jurnal Psikodimensia. Vol.7, No.1, 2638.Hofstede, G. (1980). Culture and organizations. International Studies of Management and Organizations. Vol.10, 15-41.Hughes, R.L., Ginnett, R.C., & Curphy, G.J. (2012). Leadership: Enhanching The Lesson of Experience Seventh Edition. New York: McGraw-Hill Irwin.Jones, M. L., & Alony, I. (2007). The cultural impact of information systems ?through the eyes of Hofstede ? a critical journey. Informing Science and Information Technology. Vol. 4, 407-419.Juniarari. (2011). Komitmen Organisasi. Accessed on http://juniarari.blogspot.co.id/2011/11/komitmen-organisasi.htmlKatz, D., & Kahn, R. L. (1978). The social psychology of organizations. New York: Wiley.Keskes, I. (2014). Transformational Leadership and Organizational Commitment: Mediating Role of Leader-Member Exchange. (Unpublished Thesis), Universitat Politecnica de Catalunya, Spanyol.Konja, V., Leposava, GN., & Dejan, M. (2015) The Influence of Leader-Member Communication on Organizational Commitment in a Central European Hospital. Acta Polytechnica Hungarica, vol. 12, br. 3, str. 109-128.Kotter, J. P., & Heskett, J. L. (1992). Corporate Culture and Performance. New York: Free Press.Kreitner, R, & Kinicki., A. (2007). Organizational Behaviour 7th edition. New York: McGraw-Hill Inc.Kreitner, R., & Kinicki, A. (2014). Organizational behaviour eighth edition. New York: McGraw-HillLangton, N., Robbins, S. P., & Robbins, S. P. (2007). Organizational behaviour: Concepts, controversies, applications. Toronto: Pearson Prentice Hall.Lee., J. (2004). The effect of leadership and leader member exchange on commitment. Leadership & Organization Development Journal, Vol. 26 Issue: 8, pp.655-672Liden, R. C., & Maslyn, J. M. (1998). Multidimensionality of leader?member exchange: An empirical assessment through scale development. Journal of Management, Vol.24 (1), 43-72.Liden, R. C., Sparrowe, R. T., & Wayne, S. J. (1997). Leader-member exchange theory: The past and potential for the future. Research in personnel and human resources management, Vol.15, 47-119.Liden, R.C., Sparrowe, Raymond, T., & Wayne, S.J. (1997). Leader- Member Exchange Theory: The Past and Potential for The Future. Research in Personnel and Human Resource Management, vol. 15, 47-119.Ling., H. (2012). Building employees? organizational commitment with LMX: The moderating role of supervisor support. Global Journal of Engineering Education, Vol. 14, No, 3.Lok, P., & Crawford, J., (2004). The effect of organisational culture and leadership style on job satisfaction and organisational commitment: A cross?national comparison. Journal of Management Development, Vol. 23 Issue: 4, pp.321-338.Luthans, F. (2008). Organizational Behavior. New York: McGraw-Hill.Mangkunegara, A. P. (2013). Manajemen Sumber Daya Perusahaan. Bandung: Remaja Rosdakarya.Messner, W. (2013). Effect of organizational culture on employee commitment in the Indian IT services sourcing industry. Journal of Indian Business Research 5 (2), 76-100.Meyer, J. P., Allen, N. J., & Smith, C. A. (1993). Commitment to organizations and occupations: Extension and test of a three-component conceptualization. Journal of Applied Psychology, 78(4), 538-551.Morrow, P. C., Suzuki, Y., Crum, M. R., Ruben, R., & Putsch, G. (2005). The role of leader?member exchange in high turnover work environments. Journal of Managerial Psychology, Vol.20, No.8, 681-694.Noor, J. (2011). Metode Penelitian. Jakarta: Prenada Media Group.Noordin, F., Omar, S., Sehan, S., & Idrus, S. (2010). Organizational culture and its influence on organizational commitent. International Business & Economics Research Journal 9 (2), 1-10.Northouse, P.G. (2013). Kepemimpinan: Teori dan Praktik (edisi keenam). Jakarta: PT. Indeks.Nunes, E.M.G.T., & Gaspar, M.F.M. (2013). Quality of the leader-member relationship and the organizational commitment of nurses. Revista da Escola de Enfermagem da USP, 51, e03263.Nurkholis. (2003). Manajemen Berbasis Sekolah : Teori, Model dan Apikasinya. Jakarta : Grasindo.Panggabean. S, & Mutiara (2004). Manajemen Sumber Daya Manusia. Bogor: Ghalia Indonesia.Periantalo, J., & Mansoer, W.D. (2008). Faktor-faktor yang Mempengaruhi Kesiapan Untuk Berubah Pegawai Di Dirjen PQR. JPS vol. 14, no. 03.Ping, F. S., & Yue, H. K. (2010). The Mediating Effects Of Leader-Member Exchange (LMX) And Team-Member Exchange (TMX) On The Relationship Between Emotional Intelligence, Job Satisfaction And Job Performance Of Employees. (Unpublished Thesis), Hong Kong Baptist University, Hong Kong.Porter, L. W., Steers, R. M., Mowday, R.T., & Boulian, P.V. (1974). Organizational commitment, job satisfaction, and turnover among psychiatric technicians. Journal of Applied Psychology, 59(5), 603-609.Robbins, S. P., & Coutler, M. (2012). Management. New York: Pearson.Robbins, S. P., & Judge, T. A. (2006). Organizational Behaviour tenth edition. New Jersey: Prentice Hall.Saasongu, N.E., & Ngutor I,D. (2012). The Influence of Corporate Culture on Employee Commitment to the Organization. International Journal of Business and Management. Vol. 7-10, 553.Schein, E. H (1992). Organizational Culture and Leadership. San Fransisco: Jossey-Bass Publishers.Shen, Y., Todd, J., Cody, D., Denghua, Y., Lei, Z., Yunlai, D., & Qinglin, Z. (2014). Linking perceived organizational support with employee work outcomes in a Chinese context: Organizational identification as a mediator. European Management Journal. 32. 406-412.Smither, R.D. (1994). The Psychology of Work and Human Performance. New York: HarperCollins College Publishers, Inc.Soekidjan. (2009). Manajemen Sumber Daya Manusia. Jakarta: Bumi Aksara.Spector, P.E. (2008). Industrial and Organizational Psychology: Research and Practice (fifth edition). USA: John Wiley & Sons, Inc.Steers, R. M. (1977). Antecedents and outcomes of organizational commitment. Administrative Science Quarterly, 22, 46-56.Strukan, E., & Nikoli, M. (2017). The impact of LMX Leadership theory on mutual trust and organizational commitment of employees in Bosnia and Herzegovina. IOP Conf. Series: Materials Science and Engineering 200.Sugiyono. (2013). Metode Penelitian Administrasi. Bandung: Alfabeta.Sugiyono. (2013). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta.Sujianto, A., E. (2009). Aplikasi Statistik Dengan SPSS. Jakarta: Prestasi Pustaka.Sumanto., & Hermanningsih, A. (2016). Pengaruh Budaya Organisasi Dan Motivasi Kerja Terhadap Komitmen Organisasional Pada PT. Bank Central Asia, Tbk. Kantor Cabang Utama Tangerang. Jurnal Ilmiah Manajemen dan Bisnis Vol.2, No.1.Suwarto. (1999). Perilaku Keorganisasian. Yogyakarta: Penerbitan Universitas Atma Jaya.Taurisa. M, & Ratnawati, I. (2012). Analisis Pengaruh Budaya Organisasi dan Kepuasan Kerja terhadap Komitmen Organisasional dalam Meningkatkan Kinerja Karyawan. Jurnal Bisnis dan Ekonomi, Vol.19, No.2.Tepeci, M. (2001). The effect of personal values, organizational culture, and person-organization fit on individual outcomes in the restaurant industry. Dissertation Abstracts International Section A: Humanities and Social Sciences, 62(6-A), 2238.Tosi, H. L., Rizzo, J. R., & Carroll, S. J. (1990). Managing organizational behaviour second edition. New York: Harper & Row.Umar, H. (2005). Metode Penelitian Untuk Skripsi dan Tesis Bisnis. Jakarta: PT. Raja Grafindo Persada.Usmany, T., A., Hamid, D., & Utami, N., H. (2016). Pengaruh Budaya Organisasi Terhadap Komitmen Organisasional Dan Kinerja Karyawan (Studi Pada Karyawan Pabrik Gondorukem Dan Terpentin Sukun Perum Perhutani Kesatuan Bisnis Mandiri Industri Gondorukem Dan Terpentin Ii, Ponorogo). Jurnal Administrasi Bisnis Vol.37, No.2.Wibowo, N.C., & Susanto, E.M. (2013). Pengaruh Kualitas Leader- Member Exchange (LMX) Terhadap Produktivitas Kerja Melalui Kepuasan Kerja dan Komitmen Organisasional Pada PT. Nutrifood Surabaya. AGORA vol. 1, no. 1.Wirjana, B.R., & Supardo, S. (2005). Kepemimpinan: Dasar-Dasar dan Pengembangannya. Yogyakarta: Andi OFFSET.